Refleksi Maqoshid Syariah Dalam Istinbath Hukum Progresif Terhadap Pembagian Harta Bersama Dalam Kompilasi Hukum Islam Di Indonesia - Supian Daelani (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study analyzes the implementation of Article 97 of the Compilation of Islamic Law (KHI) regarding the distribution of joint property after divorce in the Religious Courts of Bandung, Depok, Sukabumi, and Garut. This article mandates an equal division of assets between husband and wife without considering individual contributions. However, this rule is often viewed as unfair because it does not account for the specific roles in acquiring assets, particularly in the context of the evolving roles of husbands and wives, where many wives also contribute as breadwinners. Court rulings in Bandung and Depok reveal that judges have begun to consider both economic and non-economic contributions, resulting in a more proportional division of assets. In contrast, in Sukabumi and Garut, the division is still rigidly applied according to formal regulations. This highlights the need for reform. This study explores maqashid al-shariah, which emphasizes substantive justice and public welfare, as a basis for reforming Article 97 of the KHI. This reform aims to achieve a fairer distribution of assets based on each party's actual contribution. The participation of society and academics is also essential in this reform process to ensure that the policies developed are relevant and just.